Exogenous gibberellin can effectively and rapidly break intermediate physiological dormancy of Amsonia elliptica seeds - Lee, Sang Yeob; Park, Kyungtae; Jang, Bo-Kook; Ji, Boran; Lee, Hamin; Baskin, Carol C.; Cho, Ju-Sung (Frontiers in Plant Science, 2022)
Accelerated global warming is leading to the loss of plant species diversity, and ex situ preservation of seeds is becoming an increasingly important aspect of species conservation. However, information on dormancy and germination is lacking in many endangered species. Amsonia elliptica (Apocynaceae) is the only Amsonia species native to Korea, and the South Korean Ministry of Environment has designated it Class II endangered wildlife. Nevertheless, the dormancy class and the dormancy breaking method for seeds of this species for germination are not precisely known. We identified the structure of A. elliptica seeds and the causes of dormancy, which inhibits germination. In addition, we tried to develop an effective germination promotion method by testing the wet stratified condition, which breaks dormancy, and the form of gibberellin that can replace it. Fresh seeds of A. elliptica imbibe water, but the covering layers (endosperm and seed coat) inhibit germination by mechanically restricting the embryo. Initial germination tests confirmed low embryo growth potential and physiological dormancy (PD). Restriction due to the covering layer was eliminated by seed scarification, and abnormal germination was observed. After 12 weeks of cold moist stratification at 4 °C, only 12% of seeds germinated. However, 68.8% of seeds subjected to 8 weeks of warm moist stratification followed by 12 weeks of cold stratification germinated, indicating that warm stratification pretreatment before cold stratification is effective in breaking dormancy. A. elliptica seeds exhibited intermediate PD. Furthermore, 61.3% of seeds soaked in 500 mg/L GA4+7 for 14 days and incubated at 25/15 °C germinated. Therefore, GA4+7 rapidly broke the dormancy of A. elliptica seeds compared with warm plus cold stratification treatment, thus providing an efficient method for seedling production.